IMPROVING THE MECHANISM FOR MANAGING FINANCIAL RESOURCES OF LOCAL BUDGETS IN THE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Imanova Umida Baxtiyorovna (Scholar Express Journals, 2024)
This article analyzes the issues of strengthening the financial independence of local budgets in the socio-economic development of regions. In particular, it examines the scientific and practical significance of introducing a mechanism ensuring that at least 50% of personal income tax (PIT) revenues (excluding payments made by major taxpayers) are transferred to district and city budgets. The research results demonstrate that this mechanism plays a crucial role in enhancing economic activity, increasing employment, stimulating entrepreneurship, and ensuring fiscal stability in the regions.
Keywords: local budget; financial resources; personal income tax